Pemberdayaan Kader Posyandu sebagai Sumber Informasi Dasar Kesehatan Ibu Hamil - Awatiful Azza; Norita Citra Yuliarti; Andika Putra Setiawan; Danu Indra Wardana (Ali Institute of Research and Publication, 2025)
Integrated Service Post (Posyandu) cadres are the spearhead of service delivery at the most basic level. They are required to provide services to help pregnant women understand their health issues. This activity aims to analyze the effectiveness of training and health education on cadre knowledge. The research design for this community service activity used a quasi-experimental approach with a one-group pretest-posttest design. The study was conducted with 18 Posyandu cadres in Kemiri Village. The implementation phase included pre- and post-tests to assess the effectiveness of the training and health education activities. The training, using a participatory and applied approach, provided cadres with information on nutrition for pregnant women, how to identify nutritional disorders, how to assist pregnant women in meeting their nutritional needs, and knowledge about purple sweet potato-based snack foods for pregnant women. The instrument used to measure cadre knowledge was a questionnaire with 20 multiple-choice questions. Data analysis used the non-parametric Wilcoxon Signed-Rank Test. The results of the activity showed an average pre-test score for Posyandu cadres of (8.28 ± 0.57) and an average post-test score of (9.39 ± 0.85). Therefore, it can be concluded that there was an increase in the average pre-test and post-test scores for Posyandu cadres. Meanwhile, the analysis of the effectiveness of training and education on maternal nutrition on Posyandu cadres' knowledge showed a P-value of 0.001, thus concluding that training and health education effectively improved cadres' knowledge of maternal nutrition. Cadres, as the most basic service providers, must always receive the latest information to support their duties. Furthermore, the involvement of community leaders and cross-sectoral stakeholders is essential to increase community support and participation.